Insulin resistance and intestinal integrity in children with and without HIV infection in Uganda. Issue 2 (23rd October 2019) - Dirajlal‐Fargo, S; Shan, L; Sattar, A; Bowman, E; Gabriel, J; Kulkarni, M; Funderburg, N; Nazzinda, R; Musiime, V; McComsey, GA
Abstract : Objectives: The risk of cardiometabolic complications in children with perinatally acquired HIV infection (PHIVs) and in perinatally HIV‐exposed but uninfected children (HEUs) and its relationship to systemic inflammation and markers of gut integrity are not well established. In this current study, we assed insulin resitance in PHIV compared to HEUs and HIV unexposed uninfected children and explored potential association with intestinal damage biomarkers. Methods: This was a cross‐sectional study in PHIVs, HEUs and HIV‐unexposed, uninfected children (HUUs) aged 2–10 years enrolled in Uganda. PHIVs were on stable antiretroviral therapy (ART) with HIV viral load < 400 HIV‐1 RNA copies/mL. Insulin resistance was estimated using the homeostasis model assessment of insulin resistance (HOMA‐IR). We measured markers of systemic inflammation, monocyte activation and gut integrity. Kruskal–Wallis tests were used to compare markers by HIV status; Pearson correlation and multiple linear regressions were used to assess associations of the HOMA‐IR index with biomarkers of intestinal damage and translocation. Results: Overall, 172 participants were enrolled in the study (57 PHIVs, 59 HEUs and 56 HUUs). The median age was 7.8 [interquartile range (IQR) 6.39, 8.84] years, 55% were female and the median body mass index (BMI) was 15 (IQR 14.3, 15.8) kg/m 2 . Among PHIVs, the median CD4% was 37%, and 93% had viral load ≤ 20 copies/mL. PHIVs had higher waist:hip ratio, high‐density lipoprotein (HDL) cholesterol, triglycerides and HOMA‐IR index than the other groups ( P ≤ 0.02). Factors correlated with insulin resistance included higher BMI and HDL cholesterol and lower soluble tumour necrosis factor receptor I (sTNFRI) ( P ≤ 0.02). There was no correlation between any of the other inflammatory or gut biomarkers and HOMA‐IR index ( P ≥ 0.05). After adjusting for age and sTNFRI, BMI remained independently associated with the HOMA‐IR index ( β = 0.16; P < 0.01). Conclusions: Despite viral suppression, Ugandan PHIVs have disturbances in glucose metabolism. Higher BMI, and not immune activation or alteration of gut integrity, was associated with insulin resistance in this population.